Identification of novel anti-obesity saponins from the ovary of sea cucumber (Stichopus japonicus) - Hyo-Deok Seo; Ji-Young Lee; So-Hyun Park; Eunyoung Lee; Jeong-Hoon Hahm; Jiyun Ahn; A Ra Jang; So Hee An; Jang Ho Ha; Kyoung Tai No; Chang Hwa Jung (Heliyon, 2024)
The potential anti-obesity effects of sea cucumber extract have been reported. However, the individual saponins responsible for these effects are yet to be isolated and characterized. This study aimed to identify the most effective sea cucumber body part for inhibiting lipid accumulation in adipocytes and to elucidate the compounds responsible for this effect using nuclear magnetic resonance (NMR) techniques. Sea cucumber ovary 80 % ethanol extract (SCOE) demonstrated remarkable efficacy in inhibiting adipocyte differentiation compared to other sea cucumber body parts with 50 % or 80 % ethanol extracts. SCOE anti-obesity effect was evaluated in C57BL/6 mice fed a high-fat diet, which revealed significant reductions in body weight, serum lipids, adipose tissue, and liver weight. Using column chromatography, eight saponins were isolated from the SCOE, four of which exhibited potent inhibitory effects on adipocyte differentiation. Of these, three active saponins, holotoxins A, B, and D1, were newly identified. These findings highlight the potential of SCOE and its saponins as effective anti-obesity agents.